Escherichia coli resistant to tetracyclines and to other antibiotics in the faeces of U.K. chickens and pigs in 1980. - Smith, H. W. (Cambridge University Press, 1981)
A survey conducted in 1980, 9 years after the banning of the use of tetracyclines as feed additives in the U.K., indicated that table chickens and pigs were still a large reservoir of tetracycline-resistant Escherichia coli; the incidence of transferable tetracycline resistance was greater in chicken E. coli strains (68%) than in pig E. coli strains (20%). Large amounts of sulphonamide-resistant and of furazolidone-resistant E. coli were found in the faeces of chickens; E. coli resistant to both sulphonamides and streptomycin were common in the faeces of chickens and pigs. E. coli with transferable or mobilizable trimethoprim resistance were present in the faeces of most pigs and in the faeces of 10% of chickens.